(untitled) (Journal of Pakistan Orthopaedic Association, 2018)
Objective: To know the earliest age limit when surgical intervention can be avoided in Congenital Dislocated Knee. Methods: This Prospective study was carried at Jinnah Postgraduate Medical Centre Karachi, Pakistan from January 2013 to December 2016.The patients with Idiopathic, Type II & III Congenital Knee Dislocations (CDK), in newborn to three months were managed by serial manipulation and Casting with and without per Cutaneous Quadriceps Tenotomy (PCQT). Results: At 26 months median follow-up, out of 32 knees of 23 patients, 29(90.62%) behaved Excellent and 2(6.25%) behaved good. Average 4 casts required, to achieve >1200 flexion, stable knees with negative Drawers test in 96.87% Knees. The required number of casts increased from 3 to 5 as age increased from one day to one month & above, moreover 7 knees of 3 patients, who got treatment initiated after 3 weeks of birth also required PQCT. Conclusion: The CDK is easy to reduce without significant manipulation time, when treatment is started within 24 hours of birth. With increasing age from hours to four weeks, the manipulation takes more time to reduce and required more number of cast to maintain reduction. After three weeks of age, CDK often require an addition procedure of PCQT.